Liquified chitosan-alginate multilayer capsules incorporating poly(L-lactic acid) microparticles as cell carriers - Correia, Clara R. (2013)
We report the development of liquified multilayer hierarchical capsules capable of providing cell adhesion sites to the encapsulated cells. The proof of principle is demonstrated with the example of a chitosan–alginate shell via layer-by-layer assembly, encapsulating cells adhered to the functionalized surface of poly(L-lactic acid) microparticles.